HIERARCHICAL TEXT CLASSIFICATION USING DICTIONARY BASED APPROACH AND CONVOLUTIONAL NEURAL NETWORK - Ms. Sneha N. Jagtap; Amol. C. Adamuthe (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
As increasing amount of electronic information which is usually in textual form. There is an important requirement to classify textual reports generated by organizations into various categories. Machine Learning techniques can be employed to classify text autonomously in an effective manner. We propose a generic web-based application for classifying text using machine learning techniques. For creating a baseline implementation, we projected a dictionary-based approach for text classification. The dictionary is populated based on domain-specific inputs. The dictionary is expanded using automated techniques. This helps us in getting an end-to-end implementation of full pipeline. In subsequent phases, we proposed our approach with Convolutional Neural Network (CNN) for text classification.